Race and Ethnicity in East Africa - Forster, P. author. aut Link
VIII, 181 p.
Keywords: Race and ethnicity continue to be important, if unwelcome, factors in modern politics. This is evident in East Africa: the ethnic factor is often dominant in multi-party elections, while in Rwanda and Burundi bloodshed and genocidal attacks have been linked to ethnic difference. This book examines the phenomena of race and ethnicity in general, but with particular reference to Africa, especially the East. The impact of non-indigenous groups is considered, together with ethnic differences between Africans. The relevance of tourism and religion is also examined.